(untitled) (AYUSHDHARA, 2023)
Haemorrhoids, commonly known as piles, are a prevalent anorectal disorder affecting a significant portion of the population. This case report presents the successful management of second-degree internal haemorrhoids using Ayurvedic treatment, specifically Kshara karma with Apamarga pratisaraneeya Tikshna kshara. A 32 year male patient with prolapsed pile mass and bleeding during defecation was treated at the National Institute of Ayurveda, Jaipur. After a few days of initial post-operative pain and swelling, the patient’s symptoms significantly improved, with the haemorrhoids reducing in size and eventually disappearing. The post-operative complications were managed by the internal administration of Triphala guggulu, Yashtimadhu taila matravasti, and sitz bath. This case highlights the efficacy of Ayurvedic treatment, particularly Kshara karma, as an office procedure for managing haemorrhoids. The approach demonstrated reduced hospitalization, minimal bleeding, and post-operative complications, making it a promising alternative to conventional surgical procedures.